2021
DOI: 10.1186/s13041-021-00843-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of interaction between C-reactive protein and gut microbiome on the risks of anxiety and depression

Abstract: Cumulative evidence shows that gut microbiome can influence brain function and behavior via the inflammatory processes. However, the role of interaction between gut dysbiosis and C-reactive protein (CRP) in the development of anxiety and depression remains to be elucidated. In this study, a total of 3321 independent single nucleotide polymorphism (SNP) loci associated with gut microbiome were driven from genome-wide association study (GWAS). Using individual level genotype data from UK Biobank, we then calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…There is also an assumption that the development of sporadic AD might be driven by the microbiome-associated peripheral inflammation 45 . Previous studies investigating the links between gut microbiota and low-grade inflammation marker C-reactive protein found Ruminococcaceae, Akkermansia, and Lactobacillales to be associated with the risk of anxiety and depression 46 . In cardiovascular patients, peripheral C-reactive protein was linked to the abundance of Bifidobacterium, Faecalibacterium , Ruminococcus, and Prevotella 47 .…”
Section: Discussionmentioning
confidence: 98%
“…There is also an assumption that the development of sporadic AD might be driven by the microbiome-associated peripheral inflammation 45 . Previous studies investigating the links between gut microbiota and low-grade inflammation marker C-reactive protein found Ruminococcaceae, Akkermansia, and Lactobacillales to be associated with the risk of anxiety and depression 46 . In cardiovascular patients, peripheral C-reactive protein was linked to the abundance of Bifidobacterium, Faecalibacterium , Ruminococcus, and Prevotella 47 .…”
Section: Discussionmentioning
confidence: 98%
“…16S rDNA sequencing of intestinal microorganisms showed that f_Ruminococcaceae abundance increased most significantly in the immune-tolerant group ( Figure 3E ). This flora is closely related to nervous system diseases, such as Alzheimer’s disease, depression, and stroke ( Chang et al., 2021 ; Chen et al., 2021 ; Cuervo-Zanatta et al., 2021 ). Ruminococcus helps inhibit the translocation of bacterial products (e.g., LPS) into the blood, which may activate the Toll-like receptor 4 (TLR4), stimulate inflammatory responses, and secrete proinflammatory cytokines ( Shi et al., 2006 ; Cani et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antiepileptic drugs have different activating or inhibitory effects on metabolic enzymes. For example, carbamazepine, oxcarbazepine, and phenytoin can induce CYP3A4 activity ( Ghosh et al., 2018 ; Chen et al., 2021 ; Roberti et al., 2021 ), whereas levetiracetam, phenobarbital, and phenytoin induce P-gp expression ( Jing et al., 2010 ; Moerman et al., 2011 ; Alvariza et al., 2014 ). Follow- up studies can determine whether the metabolism of antiepileptic drugs is related to the expression of CYP3A1 and P-gp in the intestinal tract and whether changes in the intestinal flora of patients with epilepsy have an impact on the expression of CYP3A and P-gp in the intestinal wall and in an epilepsy model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Holdemanella may influence brain function and behavior via the microbiota-gut-brain axis. Chen et al reported previously that Holdemanella was related to a risk of anxiety (β = −0.008; P = 4.20 × 10 −3 ) and depression (β = −0.007; P = 1.39 × 10 −2 ) ( 28 ). Scheepers et al investigated the associations between natural compulsive-like behavior in deer mice and alterations in the gut microbiota and found that the prevalence of Holdemanella was associated with obsessive-compulsive disorder, a disease driven by aberrant cognitive processes ( 29 ).…”
Section: Discussionmentioning
confidence: 99%